Care Ethics Management and Redesign Organization in the New Normal - Ripamonti, Silvio Carlo; Galuppo, Laura; Petrilli, Sara; Dentali, Sharon; Zuffo, Riccardo Giorgio (Frontiers in Psychology, 2021)
The pandemic period has placed the organizations in a state of great tension. It has generated a situation of confusion, lack of rules, and production-related criticalities that have called into question the very existence of many productive realities. This article aims to highlight the dimensions of care and ethics put in place by HR managers in COVID-19. The objective that animated the authors have focused on the HRM level of medium and large companies in Italy to highlight the protective actions toward people and the organization in the period COVID 19, highlighting what were the ethical values and actions of care put in place. In this article, we wanted to give voice to managers (N = 45, including 21 women and 24 men, aged between 40 and 55 years old) who had management tasks in their organizations by asking them to tell us how they dealt with the challenges imposed by the emergency. In the research, we start from a way of understanding workplaces understood as a “process of ongoing social relationship” within which the HR function is dedicated to the care of the quality of relationships. HR managers have to manage a complex role of mediating between the interests of people and employers by trying to find good mediations.